ADMINISTRATORSâ ROLES IN TRAINING PROGRAMS AND TRAINING TRANSFER - Ismail, Azman; Hua, Ng Kueh; Ismail, Yusof; Samah, Ainon Jauhariah Abu; Bakar, Rixal Abu; Ibrahim, Nurshahira (Jurnal Dinamika Manajemen, 2015)
An administrator plays a vital role in the growth and development of his/her subordinates. Despite this notion, the role of an administrator in the context of training programs and transfer of training is not well studied. Therefore, this study is set to examine the relationship between administratorâs role in training programs and training transfer. A survey method was utilized to gather 706 survey questionnaires from employees of local authorities of three cities in the state of Sarawak, Malaysia. The results of SmartPLS path model analysis confirmed that the ability of administrators to properly implement support, communication and assignment in planning and implementing training programs has been an important predictor of training transfer in the studied organization. Further, this study provides discussion, implications and conclusion.